Analytical Functionality Model: A Drug-Clearing Operation Intervention Mechanism for the Barangay Anti-Drug Abuse Council (BADAC) - Alvin Romualdo (Mengeja Indonesia Publisher, 2022)
This study aimed to assess the BADAC in the three phases of drug clearing operations and develop an analytical functionality model of intervention mechanisms. The essence of this study is of high significance to the improvement of public safety and security as it attempts to create a baseline model encapsulating the strategies to leverage the implementation of the drug clearing operations of the barangays. It employed a sequential explanatory mixed-method research design to generate responses from the respondents and inputs from the informants in the development of a functional model. In terms of the extent of functionality of the BADAC members in the drug-clearing operations, Barangay Labangal has a very great extent of functionality with a mean of 4.45. The result from the Variance Analysis revealed that the overall drug-clearing operation has a significant difference with a p-value of .006 at 0.05 level of significance. The Confirmatory Factor Analysis (CFA) through Analysis of Moment Structures (AMOS) suggests a good model fit based on Normed Fit Index, Incremental Fit Index, Tucker Lewis Index, and Comparative Fit Index, which reached the 0.900 based reference. The analytical functionality model delineates the social environment of BADAC, which is powerfully shaped by the policies, ordinances, mandates, and strong political will. Therefore, it is recommended that coordination and concerted efforts among the law enforcement agencies, the LGU, and the community can multiply the force for effective implementation of the drug-clearing operations.